(untitled) (Medical Forum Monthly, 2024)
Objective: Methotrexate is the most commonly used DMARD by the physicians in Pakistan. It is very effective in arresting the disease process and preventing joint damage. Prolong use of methotrexate may cause some unwanted effects including hematological abnormalities which may be a cause of extra concern for the physicians and patients as well. Study Design: Descriptive/cross sectional study. Place and Duration of Study: This study was conducted at the Medical Units of Mardan Medical Complex (M.M.C) from January 2015 to December 2016. Materials and Methods: Adult 112 male and female patients with rheumatoid arthritis were enrolled in the study. American college of rheumatology (ACR) / European league against rheumatism (EULAR) diagnostic criteria was used for rheumatoid arthritis. They were given 7.5 mg of methotrexate once weekly and were followed for six months with regular monthly full blood count. Results: Out of 112 patients 23 were males and 89 were females. They age of patients ranged from 21 to 60 years. Mean age of the study population was 36.66 years. Anemia was found in six patients (5.4%), leucopenia was found in four patients (3.6%), thrombocytopenia was found in three patients (2.7%) and pancytopenia was found in only one patient (0.9%). Conclusion: Hematological abnormalities is a common side effect of low dose methotrexate and these patients require regular monitoring of blood count for detecting and treatment of these abnormalities.